2016
DOI: 10.1016/j.ceramint.2016.05.176
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and biological studies on three-dimensional porous silk/spray-dried mesoporous bioactive glass scaffolds

Abstract: a b s t r a c tThe incorporation of a bioactive inorganic phase in polymeric scaffolds is a good strategy for the improvement of the bioactivity and the mechanical properties, which represent crucial features in the field of bone tissue engineering. In this study, spray-dried mesoporous bioactive glass particles (SD-MBG), belonging to the binary system of SiO 2 -CaO (80:20 mol%), were used to prepare composite scaffolds by freeze-drying technique, using a silk fibroin matrix. The physico-chemical and biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The obtained composite scaffolds showed increased mechanical strength up to 1 MPa compared to the pure silk reference material, formation of surface hydroxyapatite after 24 h and a high ALP activity [106]. Su et al used solvent casting and particulate leaching to fabricate MBG/polyamide scaffolds that exhibited excellent biocompatibility and osteoconductivity as well as more effective osteogenesis than the reference polyamide scaffold in vivo [107].…”
Section: Compositesmentioning
confidence: 98%
“…The obtained composite scaffolds showed increased mechanical strength up to 1 MPa compared to the pure silk reference material, formation of surface hydroxyapatite after 24 h and a high ALP activity [106]. Su et al used solvent casting and particulate leaching to fabricate MBG/polyamide scaffolds that exhibited excellent biocompatibility and osteoconductivity as well as more effective osteogenesis than the reference polyamide scaffold in vivo [107].…”
Section: Compositesmentioning
confidence: 98%
“…Silk fibroin and spray-dried MBG particles were also used to fabricate porous composites by freeze-drying: compared to the pure silk constructs, the hierarchical macro-mesoporous scaffolds exhibited an improved mechanical strength (up to 1 MPa) and a fast apatite-forming ability in vitro (hydroxyapatite agglomerates visible after 1 day in SBF) [ 26 ]. Similar results were obtained incorporating MBG particles obtained by a “conventional” wet synthesis into macroporous silk scaffolds [ 27 ].…”
Section: Hierarchical Glass-based Composites Produced By “Mixing Smentioning
confidence: 99%
“…Although studies have demonstrated the preparation of micron‐sized BG powders via the spray drying method, the resulting particle sizes have been approximately 5 to 10 μm 24,25 . The size remains too small, while concave surfaces are found among larger particles.…”
Section: Introductionmentioning
confidence: 99%